Comparing indices of responsiveness for the Coma Near‐Coma Scale with and without pain items: An Exploratory study - Jennifer A. Weaver; Vera Pertsovskaya; Jasmine Tran; Allan J. Kozlowski; Ann Guernon; Theresa Bender Pape; Trudy Mallinson (Brain and Behavior, 2023)
Abstract Introduction This study aimed to establish the indices of responsiveness for the Coma/Near‐Coma (CNC) scale without (8 items) and with (10 items) pain test stimuli. A secondary purpose was to examine whether the CNC 8 items and 10 items differ when detecting change in neurobehavioral function. Methods We analyzed CNC data from three studies of participants with disorders of consciousness: one observational study and two intervention studies. We generated Rasch person measures using the CNC 8 items and CNC 10 items for each participant at two time points 14 ± 2 days apart using Rasch Measurement Theory. We calculated the distribution‐based minimal clinically important difference (MCID) and minimal detectable change using 95% confidence intervals (MDC95). Results We used the Rasch transformed equal‐interval scale person measures in logits. For the CNC 8 items: Distribution‐based MCID 0.33 SD = 0.41 logits and MDC95 = 1.25 logits. For the CNC 10 items: Distribution‐based MCID 0.33 SD = 0.37 logits and MDC95 = 1.03 logits. Twelve and 13 participants made a change beyond measurement error (MDC95) using the CNC 8‐item and 10‐item scales, respectively. Conclusion Our preliminary evidence supports the clinical and research utility of the CNC 8‐item scale for measuring the responsiveness of neurobehavioral function, and that it demonstrates comparable responsiveness to the CNC 10‐item scale without administering the two pain items. The distribution‐based MCID can be used to evaluate group‐level changes while the MDC95 can support clinical, data‐driven decisions about an individual patient.